THE ENGLISH LEARNING MOTIVATION AND ATTITUDE TOWARD ENGLISH OF D3 NURSING SCIENCE STUDENTS IN PALEMBANG, SOUTH SUMATRA - Wahyudi, Agus (Universitas Muhammadiyah Palembang, 2017)
Language proficiency is a person’s skill in using a language for a specific purpose (Richards, 1997). One of the tests used to measure the students’ English proficiency is TOEFL. The purpose of the Test of English as a Foreign Language (TOEFL) is to evaluate the English proficiency of people whose native language is not English. Over a period of three years from 2007 to 2009, one of the education Companies called Education First (EF) ranked the English proficiency among a broad population in 44 countries and territories. The results showed that Asia’s performance was lower than expected, in light of the amount spent on private English training and Indonesia was in the 34th rank or in the very low proficiency level out of 44 countries and territories in the survey (EF : 2011) There are many factors that might cause the students’ low proficiency in English, two of which are students’ motivation and attitude toward English. ‘Motivation’ is the reason or reasons behind one’s actions or behavior, it is a powerful affective variable in second language acquisition, and it has a great influence on second language learning. In order to collect the data, the researcher uses a motivation questionnaire to measure students’ motivation which consists of 40 structured questions (items) adapted from Ethel Ogane & Masako Sakamoto (1997). ‘Attitude’ is defined as a disposition or tendency to respond positively or negatively towards a certain thing (idea, object, person, or situation). In order to collect the data, the researcher uses an attitude questionnaire to measure students’ attitude. It consists of 33 structured questions (items) adapted from R. Narayanan (2008) which is developed from the Attitude/Motivation Test Battery of Gardner and Lambert and the questionnaires are calculated through Likert Scale. The population of this study is the 1st, 3rd, and 5th semester students of D3 Nursing School students which consists of 360 males and 742 females in the academic year of 2011/2012. The sample of this study consists of 91 students of 5 nursing science schools in Palembang. The result of the study shows that 25 (21.55%) students were in high motivation, 73 (62.93%) were in medium motivation, and 18 (15.51%) were in low motivation, while in attitude, it is found 21 (18.10%) in positive attitude toward English, 61 (52.60%) in neutral attitudes and 34 (29.30%) in negative attitude.